FROM NERVES TO KNOWLEDGE: CLASS ROOM ANXIETY AMONG NURSING STUDENTS AT NURSING INSTITUTES IN PAKISTAN - Saeeda Khan; Yasir Ali; Farhan Ahmed; Ghulam Mustafa; Amir Haider; Bakht Rehman; Sidra Qayyum (Journal of Population Therapeutics and Clinical Pharmacology, 2024)
Anxiety is an emotionally adaptive reaction to unclear or frightening situations that helps people act and react appropriately. Nursing students have frequently reported feeling anxious for a variety of reasons, such as the challenging nature of nursing courses and non-cooperative behavior of nursing faculty. Objectives: The objective of the study was to evaluate the level of class room anxiety among nursing students. Methodology: A descriptive cross sectional study design was used to assess the level of class room anxiety among nursing students at public and private colleges of nursing in Karachi, Pakistan from November, 2023 to January, 2024, sample size was calculated by using Open Epi version 3.0 and total 140 participants were responded while convenient sampling technique was used. A well-structured questionnaire, the Situational Communication Apprehension Measure, developed by Richmond, served as the model for the instrument used in this study to collect the data. The data was analyzed by using SPSS version 26.0. The participants of the study were the students of Generic BS Nursing above the age of 18 to 32 years while all the students of other nursing discipline were excluded from the study.Results: 20.72% of participants indicated normal range of anxiety, 28.57% shown mild to moderate level of anxiety, 42.86% reported severe degree of anxiety, and 7.85% experienced extreme degree of anxiety.Conclusion: Anxiety levels among nursing students in the classroom range from moderate to severe, Larger-scale research is still required, and interventional studies must be carried out in the future.